Highlighting the Contribution of Technological Entrepreneurship to the Dynamics of Knowledge-Based Economic Growth in the Academic Environment of Students - Mahmudin, Tono (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In the era of globalization and digitalization, economic growth increasingly relies on innovation and knowledge. Knowledge-based economies emphasize the importance of quality human resources, research, and technology to drive economic progress. The academic environment of students is one of the main centers for creating and developing new knowledge. This research aims to explore and highlight the contribution of technological entrepreneurship among students to the dynamics of knowledge-based economic growth. This study employs a literature review method with a qualitative approach and descriptive analysis. Data collection is conducted using Google Scholar as the primary source to gather scholarly articles from the period 2002-2024. The results of the study indicate that technological entrepreneurship in the academic environment of students plays a significant role in shifting the economic paradigm towards inclusive and sustainable knowledge-based growth. In an era where technology serves as the main engine of economic transformation, technological entrepreneurship opens opportunities for students to become agents of change shaping the future economy